2004
DOI: 10.1080/156142604200190261
|View full text |Cite
|
Sign up to set email alerts
|

Police Training for Democracy1

Abstract: In this paper the position is taken that the best way to prepare officers for policing based on democratic values is through an andragogy approach to training (mutual involvement of the expert and the novice in the learning process) rather than through the traditional pedagogy approach (the transmission of information from the expert to the learner). Furthermore, the education and training of police officers must be grounded in experimental learning, oriented toward problem-solving, and it must emphasize criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…It seems that a liberal value system and the ability to reflect one's own behaviour are achievements or skills that are related to a higher level of education. (Marenin, 2004; In the modern society, reflecting on one's own actions, the ability to learn new skills, flexibility and adaptability in diverse situations is becoming more and more crucial; it is also important to be able to understand the core processes behind incidents (Bergman, 2016;Nikolou-Walker & Meaklim, 2007;Sjöberg, 2016), which demands an orientation for research as well as ethical and democratic (Marenin 2004) values and the ability for lifelong learning. In the police, the connection between research and teaching is often seemingly problematic; usually, the goal is to tie academic subjects and police This article is downloaded from www.idunn.no.…”
Section: The Problematic Role Of Higher Educationmentioning
confidence: 99%
“…It seems that a liberal value system and the ability to reflect one's own behaviour are achievements or skills that are related to a higher level of education. (Marenin, 2004; In the modern society, reflecting on one's own actions, the ability to learn new skills, flexibility and adaptability in diverse situations is becoming more and more crucial; it is also important to be able to understand the core processes behind incidents (Bergman, 2016;Nikolou-Walker & Meaklim, 2007;Sjöberg, 2016), which demands an orientation for research as well as ethical and democratic (Marenin 2004) values and the ability for lifelong learning. In the police, the connection between research and teaching is often seemingly problematic; usually, the goal is to tie academic subjects and police This article is downloaded from www.idunn.no.…”
Section: The Problematic Role Of Higher Educationmentioning
confidence: 99%
“…Birzer, 2003;Bradford & Pynes, 1999;Marenin, 2004;McCoy, 2006;Vodde, 2012). Proponents of this shift have suggested that EL perspectives, albeit initially without an explicit focus on reflection, are necessary for developing communication, problem-solving, and critical thinking skills essential for community policing (e.g.…”
Section: Police Education Experiential Learning and Reflectionmentioning
confidence: 99%
“…Marenin supports this and views the ultimate goal of police training in a democratic dispensation as 'the capacity to make situational judgments which are in accord with democratic, societal and legal norms and expectations' . 22 The manner in which ethical principles are inculcated is important. 23 The traditional pedagogical learning approach was utilised in teaching limited decision-making skills to the participants in this study.…”
Section: Empowering Traffic Officials In Discretionary Decision-makingmentioning
confidence: 99%